Possible Solutions to Malnutrition Among Children Under Five as Caused By Harsh Climate Change Impacts In Uganda - Wanyina, Fred (East African Nature and Science Organization, 2025)
Malnutrition due to food insecurity is proceeding to be a strong pandemic and one of the major public health problems in developing countries like Uganda. Harsh climatic change impacts such as heavy winds, and floods, often destroy crops and cause food insecurity among households in Uganda, which in turn leads to malnutrition that affects majorly children under five. The reviewer obtained the review articles from the internet through Google search and was able to review 17 articles whose information was in line with the study of possible solutions to malnutrition caused by climate change impacts in children under five years of age in Uganda. The government and the Hospital administrators may borrow from the findings of this review study to formulate policies that may enhance the proper management of malnutrition in the country. The objectives of this review were to find possible solutions to malnutrition as brought by harsh climatic change impacts especially in children who are below five years of age, caretakers to read and put into practice the best ways of controlling malnutrition and food security practices and also communicate the findings of this review to local communities for awareness about possible solutions to get liberated from the challenge of malnutrition as pointed out by different researchers. The findings of this review included; giving attention to the risks of malnutrition and climate harsh climate change impacts, educating mothers on how to prevent malnutrition and practice good farming methods, practice of climate change mitigation and adaption; and practice of large-scale agriculture to produce more food among others. To conclude, Sustainable Development Goals spell out how we can protect our environment and slow climate change, from forests to oceans to everywhere in between. Electricity should be used and cleaner production strategies practised during farm operations. Reusing of resources must be embraced and also actions to mitigate the changing climate should be embraced and this can result in good nutrition and health, especially in children under five.